Fugitive emissions from the Bakken shale illustrate role of shale production in global ethane shift. Issue 9 (7th May 2016) - Kort, E. A.; Smith, M. L.; Murray, L. T.; Gvakharia, A.; Brandt, A. R.; Peischl, J.; Ryerson, T. B.; Sweeney, C.; Travis, K.
Abstract: Ethane is the second most abundant atmospheric hydrocarbon, exerts a strong influence on tropospheric ozone, and reduces the atmosphere's oxidative capacity. Global observations showed declining ethane abundances from 1984 to 2010, while a regional measurement indicated increasing levels since 2009, with the reason for this subject to speculation. The Bakken shale is an oil and gas‐producing formation centered in North Dakota that experienced a rapid increase in production beginning in 2010. We use airborne data collected over the North Dakota portion of the Bakken shale in 2014 to calculate ethane emissions of 0.23 ± 0.07 (2 σ ) Tg/yr, equivalent to 1–3% of total global sources. Emissions of this magnitude impact air quality via concurrent increases in tropospheric ozone. This recently developed large ethane source from one location illustrates the key role of shale oil and gas production in rising global ethane levels. Key Points: The Bakken shale in North Dakota accounted for 1–3% total global ethane emissions in 2014 These findings highlight the importance of shale production in global atmospheric ethane shift These emissions impact air quality and influence interpretations of recent global methane changes